Aspects of financial history in Romania. Reform and reformers. The financial tax reform accomplished by Nicolae Titulescu - Ciobanu, Ramona (Transilvania University Press, 2012)
This paper presents a brief history of the financial reform designed by Nicolae Titulescu at the beginning of the 1920’s. His tax reform law was formulated after thorough research of other European tax systems. He tried to implement it while he was Minister of Finance. Even though the law was adopted, it was never enacted. It met a certain amount of controversy in the Assembly of Deputies. The analysis also tries to explain the cedular tax system.
Keywords: finance; income; cedular tax; direct tax; indirect tax; tax reform